Local Extinction of Bull Kelp (Durvillaea spp.) Due to a Marine Heatwave - Thomsen, Mads S.; Mondardini, Luca; Alestra, Tommaso; Gerrity, Shawn; Tait, Leigh; South, Paul M.; Lilley, Stacie A.; Schiel, David R. (Frontiers in Marine Science, 2019)
Detailed research has documented gradual changes to biological communities attributed to increases in global average temperatures. However, localized and abrupt temperature anomalies associated with heatwaves may cause more rapid biological changes. We analyzed temperature data from the South Island of New Zealand and investigated whether the hot summer of 2017/18 affected species of bull kelp, Durvillaeaantarctica, D. poha, and D. willana.Durvillaea spp. are large iconic seaweeds that inhabit the low intertidal zone of exposed coastlines, where they underpin biodiversity and ecosystem functioning. Sea surface temperatures (SST) during the summer of 2017/18 included the strongest marine heatwaves recorded in 38 years of existing oceanic satellite data for this region. Air temperatures were also high, and, coupled with small wave heights, resulted in strong desiccation stress during daytime low tides. Before-After analysis of drone images of four reef platforms (42, 42, 44, and 45°S) was used to evaluate changes to bull kelp over the hot summer. Bull kelp loss varied among species and reefs, with the greatest (100%) loss of D.poha at Pile Bay in Lyttelton Harbor (44°S). In Pile Bay, SST exceeded 23°C and air temperatures exceeded 30°C, while Durvillaea was exposed for up to 3 h per day during low tide. Follow-up surveys showed that all bull kelps were eliminated from Pile Bay, and from all reefs within and immediately outside of Lyttelton Harbor. Following the localized extinction of bull kelp in Pile Bay, the invasive kelp Undaria pinnatifida recruited in high densities (average of 120 m-2). We conclude that bull kelps are likely to experience additional mortalities in the future because heatwaves are predicted to increase in magnitude and durations. Losses of the endemic D. poha are particularly concerning due to its narrow distributional range.